Eolian deposits of the southwestern margin of the Botucatú paleoerg: Reconstruction of the Gondwana landscape in Central Northern Argentina - Peri, Verónica Gisel (2016)
The Mesozoic Botucatú paleoerg at the southwestern margin of Gondwana includes a succession of eolian dunes cross-strata which are presently exposed in Otumpa Hills (Central Northern Argentina). Here, the architectural facies, petrology, and provenance of those rocks were studied in order to investigate depositional environments and paleoclimates. The stratigraphic sequence included basal eolian two-dimensional crescentic dunes (Slp) overlain by three-dimensional crescentic dunes of smaller scale (Smt). These were correlated with the Upper Member Rivera of the Tacuarembó Formation (Uruguay), or its equivalent in Brazil, the Botucatú Formation. These outcrops partially mark the southwestern margin of the Botucatú paleoerg along the Chaco–Paraná Basin boundary. The paleocurrents from the W, NW, and SW and the U–Pb ages of detrital zircons indicate a main Pampean cratonic and secondary Andean magmatic arc (180 Ma) source. A detrital zircon of 180 Ma by U–Pb limits a maximum depositional age at 180 Ma (Toarcian) for facies Slp. Upwards, the phreatic silcrete and calcrete indicate semiarid conditions during the Paleocene, which are correlated with the Queguay Formation of Uruguay. A saprolite paleoweathering profile, recording wet tropical–hyper-tropical climate at the Early Eocene and representing the Gondwana landscape and climate conditions, crowns the sequence. This study represents the first provenance and surface texture analysis of minerals from the Botucatú paleoerg and was instrumental to unravel past environmental and sedimentary conditions.